Self-Care in Hypertension Management: Qualitative Insights into Patient Practices and Challenges - Salami Salami; Angga Wilandika (Journal of Public Health Sciences, 2026)
Hypertension is a leading global health burden, affecting over a billion adults, yet fewer than a quarter achieve adequate control. In Indonesia, hypertension is a major contributor to cardiovascular morbidity and mortality. Patients often struggle with sustained self-care. This study explored self-care practices and barriers to hypertension management among patients, caregivers, and nurses in a primary healthcare in Bandung. A qualitative phenomenological approach was used. Twenty participants were purposively recruited, comprising seven patients, seven family members, and six nurses. Data were collected through semi-structured interviews, transcribed verbatim, and analyzed using Colaizzi’s method. Trustworthiness was ensured through credibility, dependability, confirmability, and transferability criteria. Two themes emerged. Self-care practices included medication adherence, dietary modification, physical activity, stress management, blood pressure monitoring, and smoking cessation, though these were inconsistent. Barriers included cultural dietary norms, misconceptions about medication, limited knowledge and motivation, financial constraints, and fear of complications. Hypertension self-care in Indonesia is shaped by complex cultural, social, and economic challenges. Culturally sensitive, family-centered, and nurse-led interventions are needed to strengthen self-care and improve outcomes.